Modulation of Gut Microbiota to Enhance Effect of Checkpoint Inhibitor Immunotherapy - Wu, Jianmin; Wang, Shan; Zheng, Bo; Qiu, Xinyao; Wang, Hongyang; Chen, Lei (Frontiers in Immunology, 2021)
Accumulating evidences demonstrated the crucial role of gut microbiota in many human diseases, including cancer. Checkpoint inhibitor therapy has emerged as a novel treatment and has been clinically accepted as a major therapeutic strategy for cancer. Gut microbiota is related to cancer and the effect of immune checkpoint inhibitors (ICIs), and supplement with specific bacterial species can restore or enhance the responses to the ICIs. Namely, specified bacteria can serve as the biomarkers for distinguishing the patient who will respond to ICIs and determine the effectiveness of ICIs, as well as predicting the efficacy of checkpoint inhibitor immunotherapy. Regardless of the significant findings, the relationship between gut microbiota and the effect of ICIs treatment needs a more thorough understanding to provide more effective therapeutic plans and reduce treatment complication. In this review, we summarized the role of gut microbiota played in immune system and cancer. We mainly focus on the relationship between gut microbiota and the checkpoint inhibitor immunotherapy.